Confessions : the private school murders - Patterson, James, 1947-; Paetro, Maxine (New York : Little, Brown and Company, 2013)
Tandy Angel struggles to remember key details about her passionate love affair with the handsome son of a family enemy while tackling two cases including a wrongful homicide charge against her brother and a series of murders occurring on New York's Upper West Side.
Keywords: Brothers and sisters -- Fiction; Families -- Fiction; Murder -- Investigation -- Fiction; Love -- Fiction; Mystery and detective stories; Siblings -- Fiction; Family life -- New York (N.Y.) -- Fiction; Homicide -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Romance fiction; Mystery fiction